A simple data acquisition system based on Arduino platform for non-self-sustained gas - Misiruk, I.O.; Timoshenko, O.I.; Taran, V.S.; Garkusha, I.E. (Вопросы атомной науки и техники, 2016)
A simple data acquisition system based on Arduino Nano platform is developed. Bluetooth wireless protocol is used
for data transmission. Android OS application for data visualization and recording is developed. The system was successfully
applied for acquiring data of Langmuir probe measurements in the non-self-sustained discharge with a hollow anode. Разработана простая система сбора данных на основе платформы Arduino Nano. Bluetooth протокол был ис-
пользован для передачи данных. Приложение для визуализации и записи данных разработано для операцион-
ной системы Android. Система была успешно применена для сбора данных зондовых измерений в несамостоя-
тельном газовом разряде с полым анодом Розроблено просту систему збору даних на основі платформи Arduino Nano. Bluetooth протокол було вико-
ристано для передачі даних. Додаток для візуалізації та запису даних розроблено для операційної системи Android.
Система була успішно застосована для збору даних зондових вимірювань в несамостійному газовому роз-
ряді з порожнистим анодом.